2021
DOI: 10.1164/rccm.202008-3376im
|View full text |Cite
|
Sign up to set email alerts
|

Pneumomediastinum in Acute Respiratory Distress Syndrome from COVID-19

Abstract: substantial contributions to the conception of the work as well as critical revision for the initial draft and the revised draft. All authors also provided final approval for this manuscript.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
1
16
0
Order By: Relevance
“…14 Furthermore, pneumomediastinum has been increasingly described in COVID-19 patients who are not mechanically ventilated or have a concurrent pneumothorax diagnosis. 16,[26][27][28][29][30] This radiologic finding was also observed among the observational studies of SARS and case series of influenza A patients who developed pneumothoraces without a concurrent pneumomediastinum diagnosis, regardless of IMV requirement. 22,[31][32][33][34][35] Nevertheless, pneumomediastinum may indicate the presence of severe underlying lung pathology.…”
Section: Study Characteristicssupporting
confidence: 66%
“…14 Furthermore, pneumomediastinum has been increasingly described in COVID-19 patients who are not mechanically ventilated or have a concurrent pneumothorax diagnosis. 16,[26][27][28][29][30] This radiologic finding was also observed among the observational studies of SARS and case series of influenza A patients who developed pneumothoraces without a concurrent pneumomediastinum diagnosis, regardless of IMV requirement. 22,[31][32][33][34][35] Nevertheless, pneumomediastinum may indicate the presence of severe underlying lung pathology.…”
Section: Study Characteristicssupporting
confidence: 66%
“…Pneumomediastinum is a rare complication of acute respiratory distress syndrome (ARDS), when air leaks into the mediastinum. An increased pneumomediastinum incidence, of up to 5–13%, was reported during the coronavirus disease 2019 (COVID-19) pandemic [ 1 , 2 ] and even occurred spontaneously without a history of mechanical ventilation [ 3 ], similarly to the previous severe acute respiratory syndrome (SARS)-1 [ 4 ]. Almost half of the 30 consecutive COVID-19 patients who had prolonged invasive mechanical ventilation had full-thickness tracheal lesions and pneumomediastinum [ 5 ].…”
mentioning
confidence: 99%
“…On the contrary, among 160 randomly selected invasively ventilated COVID-19 patients without pneumothorax, mortality was 78/ 160 (49 %).We recently published a systematic review on rate of barotrauma among invasively ventilated COVID-19 patients [2]. Our pooled analysis included data from 13 studies and 1814 patients [3][4][5][6][7][8][9][10][11][12][13][14][15] and we found that pooled estimate of pneumothorax rate was 10.7 % (95 % confidence interval [CI] = 6.7 %-14.7 %), while overall rate of barotrauma event was 16.1 % (95 % CI = 11.8 %-20.4 %). In addition, we found an overall mortality rate for COVID-19 patients who developed barotrauma of 61.6 % (95 % CI = 50.2 %-73.0 %), as compared with a mortality of 49.5 % (95 % CI = 41.1 %-58.0 %) for COVID-19 patients who did not develop barotrauma.We are pleased to read that our findings are further reinforced by another study, that confirms that pneumothorax rate among mechanically ventilated COVID-19 patients is between 10 and 15 %.…”
mentioning
confidence: 99%
“…We recently published a systematic review on rate of barotrauma among invasively ventilated COVID-19 patients [2]. Our pooled analysis included data from 13 studies and 1814 patients [3][4][5][6][7][8][9][10][11][12][13][14][15] and we found that pooled estimate of pneumothorax rate was 10.7 % (95 % confidence interval [CI] = 6.7 %-14.7 %), while overall rate of barotrauma event was 16.1 % (95 % CI = 11.8 %-20.4 %). In addition, we found an overall mortality rate for COVID-19 patients who developed barotrauma of 61.6 % (95 % CI = 50.2 %-73.0 %), as compared with a mortality of 49.5 % (95 % CI = 41.1 %-58.0 %) for COVID-19 patients who did not develop barotrauma.…”
mentioning
confidence: 99%